Dummy Yersinia pestis Strains: Selection Criteria, Usage Guidelines - Sazanova, E. V.; Malyukova, T. A.; Popov, Yu. A. (Problemy osobo opasnyh infekcij, 2014)
Objective of the work was to develop selection criteria for the dummy Y. pestis strains, as well as principles of the setting-up a panel and its application for practicing laboratory and differential diagnostics of plague. Studied were the RF regulations, statutory documents and methodological recommendations on the laboratory diagnostics of plague and safety of works with microorganisms; training courses for specialists to qualify for work with the agents of particularly dangerous infections. Research method: analytical. Consequently, established were the term for “dummy strain”; selection criteria for the Y. pestis strains used in the practical course within the frames of the training programme “Microbiology and Laboratory Diagnosis of Plague”; and algorithm of the course application in view of biological risk mitigation during the process of education.